Fabrication of CdS nanowires with increasing anionic precursor by SILAR method. (18th May 2016) - Dariani, R S; Salehi, F
Abstract: CdS nanowires were fabricated on glass substrate at room temperature by SILAR method with cadmium nitrate cationic and sodium sulfide anionic precursors. The deposition were done at different S:Cd concentration ratios of 1:1, 3:1, 5:1, and 7:1. Nanowires growth procedure was studied in the mentioned concentrations. The number of immersion cycles was kept constant at 15 cycles. EDX analysis showed that in all stoichiometric ratios, S/Cd composition ratio remains at about unity. Our results indicated that S:Cd concentration ratio of 7:1 had the longest nanowires with hexagonal structure. The main objective of this paper was to produce CdS nanowires with increasing concentration of sulfur.